Factor Analysis Demonstrates a Common Schizoidal Phenotype within Autistic and Schizotypal Tendency: Implications for Neuroscientific Studies - Ford, Talitha C.; Crewther, David P. (Frontiers in Psychiatry, 2014)
Behavioural and cognitive dysfunction, particularly social and communication impairments are shared between autism and schizophrenia spectrum disorders, while evidence for a diametric autism-positive schizophrenia symptom profile is inconsistent. We investigated the shared phenotype at a personality trait level, particularly its resemblance to schizoid personality disorder, as well as differential aspects of the autism-schizophrenia model. Items of the Autism Spectrum Quotient (AQ) and Schizotypal Personality Questionnaire (SPQ) were pseudo-randomly combined, and were completed by 449 (162 male, 287 female) non-clinical participants aged 18-40. A Factor Analysis revealed three factors; the first represented a shared social disorganization phenotype, the second reflected perceptual oddities specific to schizotypy while the third reflected social rigidity specific to autism. The AQ and SPQ were strongly correlated with Factor 1 (AQ: r=.75, p<.001; SPQ: r=.96, p<.001), SPQ score was correlated with Factor 2 (r=.51, p<.001), particularly in Cognitive-Perceptual features (r=.66, p<.001), and AQ score was strongly correlated with Factor 3 (r=.76, p<.001). Furthermore, there was no relationship between Factor 1 and Factor 2. Thus, there is robust evidence for a shared social disorganization phenotype in autistic and schizotypal tendency, which reflects the schizoid phenotype. Discriminating and independent dimensions of schizotypal and autistic tendency exist in Factors 2 and 3 respectively. Current diagnostic protocols could result in different diagnoses depending on the instrument used, suggesting the need for neuromarkers that objectively differentiate autistic and schizotypal traits and resolve the question of commonality versus comorbidity.